Memahami Peran Etika dan Kompetensi Konselor dalam Konseling Multibudaya - Musyaffa Dafa Firdaus; Fhito Atma Kumariaksy; Bakhrudin All Habsy (Lembag, 2025)
This article discusses the importance of counselor ethics and competencies in the context of multicultural counseling in Indonesia. Counseling, as a professional service, requires an ethical relationship between counselor and client to support individual development. By upholding ethical values, counselors can understand and appreciate the cultural differences that exist, thus being able to provide inclusive and effective services. This research uses a qualitative method with a literature study to explore the function of ethics in multicultural counseling and the barriers faced. The results showed that multicultural awareness and ethical competence are necessary to overcome challenges in counseling practice.